2015
DOI: 10.1021/acsmedchemlett.5b00143
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Discovery of Potent and Selective DDR1/2 Inhibitors

Abstract: The DDR1 and DDR2 receptor tyrosine kinases are activated by extracellular collagen and have been implicated in a number of human diseases including cancer. We performed a fragment-based screen against DDR1 and identified fragments that bound either at the hinge or in the back pocket associated with the DFG-out conformation of the kinase. Modeling based on crystal structures of potent kinase inhibitors facilitated the "back-to-front" design of potent DDR1/2 inhibitors that incorporated one of the DFG-out fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…However, the study did not address the contribution of wild-type DDR2 to oncogenesis, and while several more recent studies have confirmed the occurrence of DDR2 mutations in different patient populations [122][123][124], it is far from clear whether the mutations are indeed oncogenic and their roles in lung SCC cell signalling are undefined [125]. Notably, in other studies, some of the 'oncogenic' DDR2 mutants either seemed to play tumour suppressive functions [101], or did not contribute to cell proliferation in lung SCC cell lines [126].…”
Section: Ddrs and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study did not address the contribution of wild-type DDR2 to oncogenesis, and while several more recent studies have confirmed the occurrence of DDR2 mutations in different patient populations [122][123][124], it is far from clear whether the mutations are indeed oncogenic and their roles in lung SCC cell signalling are undefined [125]. Notably, in other studies, some of the 'oncogenic' DDR2 mutants either seemed to play tumour suppressive functions [101], or did not contribute to cell proliferation in lung SCC cell lines [126].…”
Section: Ddrs and Cancermentioning
confidence: 99%
“…Inhibitors originally developed to target the activity of BCR-ABL kinase are also potent inhibitors of the DDRs [143,144], but these drugs have a very broad specificity and are active against a number of additional kinases. Orally bioavailable small molecule kinase inhibitors with selectivity over other kinases have been developed for DDR1 and DDR2 [126,[145][146][147]. However, since kinase-independent functions have been discovered for DDR1, in particular its essential role in collective cancer cell migration and invasion [110], DDR-selective kinase inhibitors may not be effective against all DDR-dependent roles in disease progression.…”
Section: Prospects For Ddr-based Therapymentioning
confidence: 99%
“…Based on the previous predicted target, a docking study was performed to confirm the affinity of compound 1 and 2 to the predicted target computationally. The docking study was done using the X‐ray crystal structure of FAK catalytic domain (Protein Data Bank [PDB]: 4K9Y) . The potent FAK inhibitor, TAE226, was also docked using the same procedure to establish a control binding to the enzyme active site.…”
Section: Resultsmentioning
confidence: 99%
“…The ligands were built by using the builder tool of the MOE program and were subjected to energy minimization (MMFF94x, gradient: 0.05) . The crystal structure of FAK catalytic domain (PDB:4K9Y) was imported from PDB . The downloaded protein was prepared by adding the missing hydrogens and bonds.…”
Section: Methodsmentioning
confidence: 99%
“…It shows that the benzene group of dasatinib positions itself deep in the ATP‐binding cleft. Murray et al . reported the X‐ray crystal structures of DDRs with dasatinib (PDB ID: 5BVW).…”
Section: Introductionmentioning
confidence: 99%